An investigation into responsible tourism practices in the South African hotel industry - M. Van Der Merwe; A. Wöcke (South African Journal of Business Management, 2007)
This paper sheds light on the reasons for the limited uptake of responsible tourism initiative memberships by hotels in South Africa, despite South Africa being regarded as a leader in the field of responsible tourism policy, with the drafting of responsible tourism guidelines by the South African Department of Environmental Affairs and Tourism (DEAT). The International Centre for Responsible Tourism's conference (hosted in South Africa) preceding the World Summit on Sustainable Development in 2002 resulted in the Cape Town Declaration, which was based on the guidelines developed by DEAT. There are currently two responsible tourism membership initiatives in South Africa. Non-experimental survey research was conducted among hotels about their understanding and implementation of responsible tourism practices. Sixty hotels responded to the survey, and it would appear that these hotels implement Corporate Social Responsibility/responsible tourism, though to varying extents. Many responding hotels do not participate in responsible tourism initiatives because of - amongst others - confusion about what the concept means, and a lack of awareness of such initiatives. This paper raises questions about the effectiveness of membership initiatives in promoting the implementation of responsible tourism practices and questions the importance of a common understanding and awareness of what responsible tourism entails in ensuring that policy is implemented.
Keywords: 650